Complex rehabilitation of traumatized permanent teeth in the aesthetic zone - Réka Miklós; Róbert Kemper (Hungarian Dental Association, 2021)
The aim of this case study is to present our treatment method for the restoration of traumatic lesions of teeth following a bicycle accident. Four upper incisors were injured; thus, special consideration was required in timing of the treatment sequence. The prognosis for teeth #11, 12, and 22 was discouraging; furthermore, due to accident, tooth #21 suffered additional rotation and discolouration. In order to preserve the original form and the aesthetics of the mucosa as well as the height of the interdental papillae, immediate implant placement in combination with the socket shield technique were chosen. To accommodate the timing and the state-of-art realisation of the surgical procedure, placements of the three implants were divided into two separate sessions . Whilst immediate replacement of tooth #11 was possible, the placement of the two other implants was only feasible after a healing period of three months. Temporary crowns were placed to preserve aesthetic mucosal margins and the emergence profiles prior to impression, which was taken using individualised custom impression copings. A pressable ceramic veneer was chosen to hide the discolouration of tooth 21. The outcome shows suitable aesthetic, stable soft tissues, preserved emergence profiles, metal-free screw-retained implant crowns, and a veneer, all of which confirm the correct choice for the treatment modality.